Hubungan Antara Konsumsi Makanan Fast Food Dengan Kejadian Obesitas Pada Remaja - Iis Sumiyati; Anggriyani Anggriyani; Akhmad Mukhsin (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Currently obesity is one of the health problems at home and abroad. Obesity in adolescents reaches 18%, in addition, adolescents also tend to consume fast-food and softdrink to create a modern self-image in their communities and obesity is the impact of excess energy consumption in Indonesia. To find out the relationship of fast-food consumption habits with obesity in adolescents. This research uses analytical research with a cross sectional approach. The population of this study was all students of Yappika Legok Vocational School, a sample used by 70 respondents and sampling techniques in each class by proportionate stratified random sampling. The analysts used are univariate and bivariate analysts with chi square tests. The results of the study obtained from 70 respondents the majority of fast-food consumption who are often obese by (81.8%) with pvalue = 0.000 means there is a relationship between fast food consumption and the incidence of obesity in adolescents in Yappika Legok Vocational School. Adolescence is still high consumption of fast food so that it makes the teenager obese, it is recommended for health workers to be more active in providing counseling and promotion about healthy lifestyles in adolescents to schools to increase knowledge, especially eating menu in accordance with daily energy needs, thus reducing the incidence of obesity in adolescents.